The Portrayal of Culture and Intercultural Competence in the English Textbook for Senior High School Level in Indonesia - Nuha, Ulin; Nuralim, Ahmad (Journal of English Teaching and Learning Issues, 2024)
Cultural components or elements in textbooks are essential in supporting intercultural competence. By providing textbooks with text containing cultural elements and cross-cultural competence, a language learner is not only prepared linguistically but also culturally. Some English textbooks in Indonesia emphasize cultural and intercultural competence to support their content, as proficiency in English requires intercultural competence. Therefore, it is necessary to analyze cultural and intercultural competence in a textbook. A descriptive qualitative method and content analysis technique are used in this research. The theories used to analyze the textbook are Xiao's, Cortazzi and Jin's, and Byram's theories. The textbook analyzed is an English textbook entitled “Bahasa Inggris” 2018 grade XII issued by the Ministry of Education and Culture of the Republic of Indonesia. This research shows that there are cultural contents depicted in several cultural themes, they are Big “C” and little “c” culture, by using Xiao’s theory. Then, by using Cortazzi and Jin’s theory, they represent 3 types of culture, namely source culture/local culture, target culture, and international culture. According to Bryram’s theory, intercultural competence has been found in the form of pictures, texts, and tasks. This competence includes knowledge, skills, and attitudes. The display of cultural themes in the textbook dominates. The results of intercultural competence showed that the skills category dominates, but critical cultural awareness is not found. The cultural contents represented in the textbook mostly adopt Indonesian local culture, and the textbook has met the competence categories required by the Ministry of Education and Culture of the Republic of Indonesia, even though it has not met the intercultural competence category conceptualized by Byram because of the absence of critical awareness category on task material in the textbook.